Easy synthesis of photoluminescent N-doped carbon dots from winter melon for bio-imaging - Feng, Xin; Jiang, Yaoquan; Zhao, Jingpeng; Miao, Miao; Cao, Shaomei; Fang, Jianhui; Shi, Liyi (RSC advances, 2015)
N-doped carbon dots were successfully synthesized via a one-step hydrothermal method by using edible winter melon as the source material. Mono-dispersed CDs 4.5–5.2 nm in diameter were achieved in a quantum yield (QY) of 7.51%. The photoluminescent CDs were demonstrated to be effective bio-imaging agents for hepG2 (liver hepatocellular carcinoma) cells.